INOVASI PELATIHAN BERBASIS TEKNOLOGI DIGITAL DI BALAI PELATIHAN VOKASI DAN PRODUKTIVITAS (BPVP) BANDUNG BARAT: STUDI EVALUATIF DAN REKOMENDASI STRATEGIS - Mochamad Sarif Hasyim; Doni Mardiyanto; Adi Masliardi (JURNAL ILMIAH EDUNOMIKA, 2026)
In the context of human resource development (HRD), technology-based training innovation is key to improving access, efficiency and the effectiveness of learning. The West Bandung Vocational and Productivity Training Centre (BPVP), as a training institution which was established and operated by the government, has begun to implement various digital approaches in its training programmes, in line with the increasing demands of an increasingly digitalised labour market. This study aims to evaluate the effectiveness of digital technology-based training at the Vocational and Productivity Training Centre (BPVP) in West Bandung, Indonesia. The study employs a descriptive-evaluative approach using mixed methods, involving a survey of training participants as well as structured interviews with management, instructors, and programme developers. The research findings indicate that digital training offers ease of access and flexibility, yet still faces challenges regarding infrastructure, instructors’ digital literacy, and the interactivity of the training materials. Strategic recommendations include strengthening infrastructure, training for instructors, the development of industry-based digital curriculum, and a data-driven evaluation system. This research makes a significant contribution to the development of vocational training policies that are adaptable to digital transformation in Indonesia. Keywords: Human Resource Development, Technology-based Training, Vocational Training